(untitled) (Revista Espinhaço, 2019)
The characterization of hydrological basins and the development of environmental evaluation tools to subsidize the sustainable management of water resources require interdisciplinary approaches. The aim of this study was to integrate ecological and geographic metrics to evaluate water quality in the Velhas river basin, a tributary of the São Francisco river (Minas Gerais, Brazil). For that it was used data on the composition of benthic macroinvertebrate assemblages of 19 different tributaries in the Velhas river basin. Geographic information was acquired for each of the sampling site drainage sub-basins, consisting of urban and rural population density, sanitary infrastructure and land use and cover. These metrics were synthesized through a Principal Component Analysis (PCA) and the associations between ecological and geographical metrics were analysed using linear regressions, with the three most representative axes of PCA as predictors synthesizing: (i) urban influence (44.37%), (ii) rural influence (16.88%), and (iii) influence of natural coverage (14.63%). The models generated for the biological metrics Richness, diversity of Shannon-Wienner, BMWP, ASPT and % of Oligochaeta showed a significant correlation (R2 ≥ 44-90, p <0.002) and all were dependent on the first axis of the PCA, evidencing that the biological metrics are sensitive to urban pressures. We conclude that urbanization is the main cause of degraded water quality in the Velhas River hydrological basin, with potential to compromise it for the entire São Francisco River basin.